Provisional Agenda for the Sixteenth Meeting of the International Monetary and Financial Committee. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The following is the provisional agenda for the Sixteenth Meeting of the International Monetary and Financial Committee, which is to be convened on Saturday, October 20, 2007, at the Fund's Headquarters in Washington, D.C.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Agenda; PP